2013
DOI: 10.1021/ol400229z
|View full text |Cite
|
Sign up to set email alerts
|

Unsupported Nanoporous Gold Catalyst for Highly Selective Hydrogenation of Quinolines

Abstract: For the first time, the highly efficient and regioselective hydrogenation of quinoline derivatives to 1,2,3,4-tetrahydroquinolines using unsupported nanoporous gold (AuNPore) as a catalyst and organosilane with water as a hydrogen source is reported. The AuNPore catalyst can be readily recovered and reused without any loss of catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 51 publications
0
58
0
2
Order By: Relevance
“…This method complements a recently presented reduction protocol that uses a nanoporous gold catalyst. 20 The hydrogen atoms in the reduction products arise from hydrosilane (2 C-H bonds on C2 and C4) and from EtOH (C-H bond at C3 and N-H bond). Furthermore, an unexpected exchange of Si-H hydride by protons from solvent can occur under the reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method complements a recently presented reduction protocol that uses a nanoporous gold catalyst. 20 The hydrogen atoms in the reduction products arise from hydrosilane (2 C-H bonds on C2 and C4) and from EtOH (C-H bond at C3 and N-H bond). Furthermore, an unexpected exchange of Si-H hydride by protons from solvent can occur under the reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While our research efforts towards this goal using supported Au NPs were in progress and had reached a level of maturity, an efficient method for the reduction of quinolines by hydrosilanes catalyzed by an unsupported nanoporous gold catalyst was reported. 20 Herein, we present our results which employ hydrosilanes/ethanol as the reducing system under solvent free conditions and Au nanoparticles supported on TiO 2 as the most suitable catalyst. In addition, a stepwise pathway was established with an initially fast 1,2-reduction mode to form 1,2-dihydroquinolines, while the new C2 and C4 hydrogen atoms on reduction products arise from the hydrosilane as supported via labelling experiments.…”
mentioning
confidence: 99%
“…Inspired with these results, the same group turned attention to the reduction of quinoline separately. 50 Solvents such as dimethyl formamide and acetonitrile, which were successfully utilized in alkyne reduction, were first studied, but the use of these solvents resulted in low yield of 1,2,3,4-tetrahydroquinoline. After screening of solvents, toluene proved to be the best and gave 91% yield of the desired product (Scheme 13).…”
Section: Hydrogenation Of Quinolinesmentioning
confidence: 99%
“…The successful reduction of C]N bond incorporated in aromatic ring such as quinoline 50 inspired us to investigate the reduction of C]N bond of imines. 51 We have found that imines can be reduced selectively with AuNPore/H 2 O/silane system.…”
Section: Hydrogenation Of Imines: An Exclusive Chemoselectivitymentioning
confidence: 99%
“…Examples of transfer hydrogenation catalytic systems active in water for promoting the selective reduction of quinolines and quinoxalines are those based on: a Ni-Al alloy [34], an Ir complex with HCOONa as the hydrogen source [35], a Pd/C and Zn mixture [36], being the majority of transfer hydrogenation catalysts active and selective only in commonly used organic solvents (alcohols, toluene, etc.) [37][38][39][40][41][42][43][44]. However, the major problem related to the recyclability of these transfer hydrogenation catalytic systems in water remains unsolved and the development of more effective, recyclable, and handle-convenient catalysts for this transformation is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%